PENINGKATAN KAPASITAS SISWA SMAN 1 PAJANGAN BANTUL DENGAN STRATEGI DIGITAL MARKETING - Sur Yanti; Hera Wasiati; Ronny Agung Hendrawan; Ariesta Damayanti; Danny Kriestanto (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
The advancement of digital technology has transformed communication and marketing patterns, requiring young generations to acquire digital marketing skills. This Community Service Program (PkM) was conducted at SMA 1 Pajangan Bantul to equip students with digital marketing literacy through both theoretical and practical training. The methods included lectures, workshops on Instagram, WhatsApp Business, and Photo Room applications. Participants were also introduced to content creation strategies, social media analytics, and TikTok Affiliate implementation. The results indicate an improvement in students’ knowledge and skills in creating digital content, managing business accounts, and understanding online marketing strategies. Positive responses from students and the school highlight the relevance of this training and the need for its continuation with more diverse topics. The program successfully prepared students not only to understand digital marketing concepts theoretically but also to acquire practical skills applicable in business and entrepreneurship.